The Impact Of Compensation And Work Environment On Employee Performance Through Job Satisfaction - Zulher Zulher; Suarni Norawati; Zahmir Basem; Ulul Azmi (Komunitas Dosen Indonesia, 2022)
This research seeks to discover the impact of compensation and office environment on employee performance as well as their overall sense of fulfillment. This is accomplished by including job satisfaction as a secondary variable in a regression analysis. Analysis of data comes from secondary research files and questionnaires. The most important data comes from the Smart PLS Version 3 SEM model. That data type is called primary data. The study proves that employee performance is affected by compensation, while the work environment has no effect on performance. However, compensation affects employee job satisfaction, while the work environment has no effect on it. Additionally, this study reveals that job satisfaction has an effect on the relationship between compensation and performance on work environment— leading to improved employee performance